Indigenous peoples as media audience an analysis of media use of the Dumagat tribe in Sitio Quinao Brgy. Puray Rodriguez, Rizal - Zafra, Norman Sulit author; Khan, Rachel E. (Quezon City University of the Philippines Diliman, 2012)
"This study examines the uses and gratifications of media by indigenous people in Sitio Quinao, a small tribal community of Dumagat people in Rodriguez, Rizal. It focuses on Dumagats not as objects or subjects of media texts but as listeners, viewers and consumers of mass media, a phenomenon brought by the changing political and socio-economic profile of cultural and indigenous groups in the Philippines. Guided by the principles of uses and gratifications theory by Elihu Katz and Jay Blumler, the social uses of media by Dennis McQuail, encoding-decoding theory of Stuart Hall and hierarchy of needs by Abraham Maslow, it tackles the influences of media on Dumagats, particularly in their lifestyle, culture and language within the context of everyday life. This research uses a combination of qualitative and quantitative methods such as structured questionnaire, focus group discussion and focus interview. Results show that several media are available in the locality, however, radio is the only medium that reachers Sitip Quinao. They consume news and information programs, weekly drama series and FM programs. The uses and gratification vary from information on weather and agriculture, entertainment, companionship, source of advice and escape from routine problems. Their radio consumption also changed their idea of time."
Vita.
Thesis
Keywords: Indigenous peoples and mass media -- Philippines -- Sitio Quinao (Rodriguez, Rizal); Indigenous peoples -- Philippines -- Sitio Quinao (Rodriguez, Rizal).; Dumagats -- Philippines -- Sitio Quinao (Rodriguez, Rizal).